Purificación de agua local para consumo humano con un destilador solar de alta eficiencia para entornos domésticos rurales áridos. - Jiménez Garcia, Karina Elizabeth (2020)
The project focuses on social development in rural areas due to the lack of access to safe drinking water. The population of San José de Pichul is isolated from the benefits of society and does not receive a solution from the authorities to meet its needs for clean drinking water. Different types of solar distillers using the greenhouse effect were considered for the development of a locally designed and built distilleries. A new process for water purification was implemented with greater emphasis on energy efficiency and low cost, opting for the hut type distillery. The San José de Pichul sector is provided with deep-well water reaching a coliform treatment system. The water proved to be unsuitable for human consumption due to its high salt content and is not properly treated, putting the health of the inhabitants at risk. This project aims to verify through solar energy if the distillation and purification system provides vital liquid suitable for human consumption. The use of renewable solar energy is fundamental in the heating of the distiller's system by the use of the evaporation and condensation stages. The process involved 2 households of 5 members each in which an online survey was conducted in the SURVEYMONKEY program, determining that the volume of water for consumption required by a person per day is 3lt/day. Once the equipment started operating, data was collected on the distilled water produced by the system during May and June 2020. The data was complemented by the satellite program SOLCAST, to help evaluate the efficiency of the distillery. Water production of 2 liters/day/m2 with minimum radiation of 100Wh/m2 and 5 liters/day/m2 with maximum radiation of 8000Wh/m2 was recorded. For the water quality, physical chemical and microbiological analysis of the water were conducted, finding that the values were for, Dissolved Oxygen 9.3 mg/l, Ph 7.91, Electrical conductivity 7.8 uS/cm, Fecal Coliforms 0, Total hardness 144mg/l, color 1.7, Turbidity 0.9 NTU, Nitrites 0 mg/l and Nitrates 5 mg/l. The solar distillation was able to transform water with high salt contents not suitable for human consumption into the water with characteristics suitable for human consumption and the parameters analyzed for the distilled water are within the maximum permissible limits of the TULSMA and INEN 1108 regulations.